Lack of Intimacy Prospectively Predicts Breakup. Issue 4 (May 2021) - Park, Yoobin; Impett, Emily A.; Spielmann, Stephanie S.; Joel, Samantha; MacDonald, Geoff
In this prospective longitudinal study, we examined whether and how lack of intimacy or meaningful connection to a romantic partner (i.e., low social reward) and concerns over negative evaluation by the partner (i.e., high social threat) each predict dissolution of a relationship as well as adjustment when a breakup occurs. Our results showed that those who perceived lower levels of reward during the relationship were more likely to experience a breakup. This effect remained significant controlling for global relationship satisfaction and individual differences in attachment insecurity. The degree of reward also predicted experiencing less emotional attachment to the partner (now an ex-partner) postbreakup, but this effect diminished when controlling for satisfaction. In contrast, threat perceptions during the relationship did not predict breakup or emotional attachment to the ex. Our findings suggest that reward perceptions during the relationship have important consequences for relationship dissolution. Implications for breakup recovery are discussed.